Use of Bacillus strains with protease, keratinase and collagenase activity in the processing of agricultural products - Maduahasova, A.; Baltin , K.; Bizhanova, B.; Khassenov , B.; Aktayeva, S. (Eurasian Journal of Applied Biotechnology, 2025)
The significant accumulation of protein-rich agro-industrial waste requires the urgent development of biotechnological methods for its processing and usage. Strains of B. subtilis and B. paralicheniformis were isolated and identified from soil samples obtained from a chicken farm in the Akmola region and the city of Taraz. These strains produce proteases with peak activity at 70 °C and pH 10.5 for B. subtilis, and at 60 °C and pH 9.0 for B. paralicheniformis. The protease, keratinase, and collagenase activity of B. subtilis enzymes are 158.8 ± 2.5 U/mL, 109.3 U/mL, and 10.4 U/mL, respectively. The enzyme values for B. paralicheniformis were 323 ± 4.8 U/mL, 122.6 U/mL, and 23.6 U/mL, respectively. Enzymatic hydrolysis of poultry and livestock waste, including chicken feathers, hooves, and cattle hides, was conducted using the B. paralicheniformis strain. Following 96 hours of treatment, the hydrolysis rates of feathers, hooves, and hides were 100%, 29.6%, and 97.2%, respectively. Examination of the hydrolyzed feathers using scanning electron microscopy revealed the degradation of essential structural components of the feathers and the adherence of bacterial cells to the surface of the feather keratin. The acquired data suggest the potential of the B. paralicheniformis strain as a producer of alkaline proteolytic enzymes and its use in technologies for processing protein-rich agro-industrial waste.